Form of Social Emotional Guidance Method for Children with Intellectual Disability in Improving Social Skills at SLB Mutiara Hati Medan Tembung - Khairunnisa Khairunnisa; Muaz Tanjung; Kamalia Kamalia (Universitas Muhammadiyah Enrekang, 2023)
This research is motivated by the condition of mentally retarded children, which needs to be discussed in the process of developing social skills. This research uses this type of research, which is qualitative research. Qualitative data is data in the form of words, sentences, gestures, facial expressions, charts, images and photos. The aim of this research is to determine the forms of social emotional guidance for mentally retarded children in improving social skills at SLB Mutiara Hati Medan Tembung and to find out the supporting and inhibiting factors in developing the social skills of mentally retarded children at SLB Mutiara Hati Medan Tembung. This writing uses a qualitative descriptive method which is useful for providing information, facts and data regarding the mentor's efforts in developing the social skills of mentally retarded children at SLB Pearl Hati Medan Tembung. The research results are (1) Guidance methods in developing the social skills of mentally retarded children (a) Methods for developing questioning skills. (b) Efforts to develop skills in establishing and maintaining friendships. (c) Methods for developing collaboration skills. (d) Methods for developing sharing skills. (e) Skills methods in religion. (2) Supporting and inhibiting factors in developing the social skills of mentally retarded children.